Pemanfaatan Sari Tapai Ketan Hitam dalam Pembuatan Cocoghurt yang Dibuat dengan Penambahan Lactobacillus plantarum 1 R.1.3.2 - Atasyavira, Nadya; Yusmarini, Yusmarini (Jurnal Teknologi dan Industri Pertanian Indonesia, 2024)
Cocoghurt is processed coconut milk fermented using lactic acid bacteria. One of the food products that can improve the quality of cocoghurt is the addition of black glutinous rice tapai juice. The purpose of this research was to obtain the right concentration of black glutinous rice tapai juice. The research was conducted experimentally using a completely randomized design with four treatments and four replicates. The treatments consisted of TKH1 (without addition of black glutinous rice tapai juice), TKH2 (addition of 10% black glutinous rice tapai juice), TKH3 (addition of 20% black glutinous rice tapai juice), and TKH4 (addition of 30% black glutinous rice tapai juice). Data were analyzed statistically using analysis of variance (ANOVA), if F count F table, it was continued with duncan's multiple range test (DMRT) at the 5% level. The results showed that the addition of black glutinous rice tapai juice had a significantly affected the degree of acidity (pH), total lactic acid, total LAB, protein content, sensory analysis (color, aroma, taste, viscosity) but did not significantly influence the ash content and fat contents. The selected treatment obtained was TKH3 = addition of 20% black glutinous rice tapai juice with a pH value 4.52, total lactic acid of 0.83%, total LAB of 10.28 log CFU/ml, ash content of 0.87%, protein content of 6.78%, fat content of 13.23%, with a description of whitish purple color, coconut milk and tapai aroma, tapai taste, and watery, as well as the overall hedonic assessment liked by panelists.